A descriptive study on the oral hygiene practices of Filipino children aged 0-3 in the Philippine Children's Medical Center - Camello, Karla Patricia B.; Dellota, Michelle Trina A.; Salinda, Ma. Cecilia G. (Adviser).
Dental caries continues to be a major dental public health problem in the Philippines, especially among younger children. Unfortunately, to date, there is no published study regarding the oral hygiene practice of Filipino children, one of the many contributing factors to dental caries. The aim of this study was to determine the oral hygiene practices of Filipino children aged 0-3 in the Philippine Children's Medical Center (PCMC). Thirty-two parents and/or caregivers were recruited from the Pediatric Dental Department of PCMC and were surveyed. Using a descriptive study design, structured questionnaires were used to elicit information on the oral hygiene practices of Filipino children. Results showed that 96.9% of the subjects were aware of the parents'/caregivers' responsibility in delivering oral hygiene regimen to their children. Also that the following are oral hygiene practices performed by or on Filipino children: toothbrushing without dentifrice, toothbrushing with dentifrice, swabbing with cotton/gauze/cloth, rinsing with water, or combination of toothbrushing with swabbing of oral soft tissues with gauze. Frequency of doing oral hygiene procedures ranges from thrice a day to less than once a day.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Children -- Dental care -- Philippines; Mouth -- Care and hygiene; Oral health